2002
DOI: 10.1063/1.1513310
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance molecular photography

Abstract: A procedure is described for storing a two-dimensional (2D) pattern consisting of 32×32=1024 bits in a spin state of a molecular system and then retrieving the stored information as a stack of nuclear magnetic resonance spectra. The system used is a nematic liquid crystal, the protons of which act as spin clusters with strong intramolecular interactions. The technique used is a programmable multifrequency irradiation with low amplitude. When it is applied to the liquid crystal, a large number of coherent long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 18 publications
1
34
0
Order By: Relevance
“…However, the ten-spin cluster used for our numerical simulations is too small to reproduce all the features of collective coherent response signals. For example, the unusual behavior observed in experiments with two consecutive weak pulses, the second one, having a 90 • phase shift [2], was not reproduced in our simulations. It should be noted that the simulations presented in this work do not account for the effect of relaxation; instead, a common line-broadening factor is used in the step of Fourier transform to yield frequency domain spectra.…”
Section: Resultsmentioning
confidence: 48%
See 2 more Smart Citations
“…However, the ten-spin cluster used for our numerical simulations is too small to reproduce all the features of collective coherent response signals. For example, the unusual behavior observed in experiments with two consecutive weak pulses, the second one, having a 90 • phase shift [2], was not reproduced in our simulations. It should be noted that the simulations presented in this work do not account for the effect of relaxation; instead, a common line-broadening factor is used in the step of Fourier transform to yield frequency domain spectra.…”
Section: Resultsmentioning
confidence: 48%
“…As an example, it has been demonstrated experimentally [2] that the NMR signal of a cluster of 19 nuclear spins contained more than one kilobit of information. Now let us discuss an excitation by a weak monochromatic external field.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We begin by outlining the general design criteria: 38,41,45 (1) Nuclei having spin magnetic moment I D 1/2 with either a high natural abundance, or using labelled samples, and having a relatively large sensitivity (the most common nuclei are 1 H, 13 C, 15 N, 19 F and 31 P); (2) compounds should be either soluble in some common NMR solvent or naturally found in a liquid state (although recent articles have shown that liquid crystals 47 and solid-state systems 48 -51 can be used); (3) the differences in chemical shifts of the nuclei should be as large as possible (this is commonly achieved by using nuclei with a large range of chemical shifts, such as 13 C and 19 F, and/or heteronuclear spin systems since separate r.f. channels can be used for each nucleus); (4) spin-spin coupling between nuclei should be large; (5) the chosen nuclei, although not required to be mutually coupled, must form a contiguous network of couplings; (6) the chosen system must have sufficiently long relaxation times to limit decoherence in addition to allowing for the evolution of implemented gates (spin-spin relaxation times, T 2 , are typically shorter than spin-lattice relaxation times, T 1 , and while it is the limiting factor it can be of the order of seconds, time enough for up to 10 14 gates).…”
Section: Introductionmentioning
confidence: 99%
“…In this physical way, other different solutions (Bennewitz et al, 2002;Kirikosian et al, 2003) are proposed and authorize even more efficient storing of information. For example, with the reading of proton spins in the hydrocarbon chain by nuclear magnetic resonance (NMR), a density of storage 100 times greater is obtained (Khitrin et al, 2002).…”
Section: Met-tyr-thr-pro-arg-leu-cysmentioning
confidence: 99%